PERILAKU KONSUMTIF BELANJA ONLINE; E-COMMERCE SHOPEE PADA MAHASISWA PEREMPUAN PENDIDIKAN SOSIOLOGI UNIVERSITAS SULTAN AGENG TIRTAYASA - Sri Rahayu Ningsih; Haryono Haryono (Yayasan Literasi Sains Indonesia, 2025)
The development of technology has brought significant changes to human life, including the ease of accessing information and services via the internet. One form of adaptation of this technology is e-commerce, which allows buying and selling transactions to be carried out online. Shopee, as one of the largest e-commerce platforms, offers various conveniences such as flexible payment methods, attractive promotional programs, and direct home delivery. However, this convenience also encourages consumer behavior, especially among the younger generation, including students. Thi aim of this study is to examine the consumer behavior of students in shopping online through Shopee, with a focus on the factors that drive this behavior and its impact on lifestyle and financial conditions. The study was conducted on students of the Sociology Education Study Program at Sultan Ageng Tirtayasa University, aged 19-23 years who actively use the Shopee application. The findings are expected to provide insight into students' digital consumption patterns, factors that trigger consumer behavior such as aggressive promotions and impulsive purchases, and their implications for financial balance. These findings contribute to the understanding of the impact of e-commerce on consumer behavior in the digital era and become the basis for formulating strategies to overcome its negative impacts, such as waste and financial problems, especially among students. This study has limitations in the scope of the subjects, namely students in one study program and the Shopee platform, so the results cannot be generalized to a wider context.